The Impact of Technology on Online Reviews and Ratings Among Muhammadiyah University Students - Zelin Wahyuni; Ghaefira Nur Fatimah (EDU PARTNER INDONESIA, 2024)
Technology and the internet have developed into a lifestyle for almost all levels of Indonesian society. The access method is very easy and its use is unlimited to get the essential data. The cause for these shifts in consumer behavior is the convenience of internet buying. Data on the value of e-commerce transactions in Indonesia, which is growing annually, further supports the convenience of purchasing. Online customer reviews influence online product purchases. This variable is thought to have an impact on prospective online buyers, where prospective buyers obtain information or advice about the product they want to buy from previous buyers of the product and experience the benefits of the product. Consumers can easily learn and read reviews that have been given as consideration when wanting to buy a product. Before making sure the item (Ika Sugiarti and Iskandar 2021) is purchased. A rating may also be defined as a user's or consumer's evaluation of a product's preference based on their transactions and experiences with it. Online shop users see the main thing, one of which is the fulfillment of needs, satisfaction or pleasure, when they have entered a feeling of satisfaction then they have Of course everything will be done to meet these satisfaction needs.